A 3D non-hydrostatic model for wave interactions with structures using immersed boundary method. (30th May 2019) - Ai, Congfang; Ma, Yuxiang; Yuan, Changfu; Dong, Guohai
Highlights: A 3D non-hydrostatic model for wave-structure interactions is developed. Validations of the general boundary-fitted non-hydrostatic model are presented. Solitary wave incident on a suspended horizontal plate is predicted by the model. Vortex-related velocity field around the structure is presented in some cases. Abstract: Immersed boundary (IB) method is incorporated in a three-dimensional (3D) non-hydrostatic model for predicting wave-structure interactions. The model solves the Navier–Stokes equations by means of an explicit projection method. The 3D grid system is built based upon a horizontal Cartesian grid framework and a vertical general boundary-fitted coordinate system. The vertical grid system not only has the boundary-fitted properties of better fitting the bed and free surface, but also allows for a great adaptability of the vertical discretization. The numerical model is validated against the experimental data of wave interactions with various types of structures including submerged bottom-mounted structure, suspended structure, and surface-piercing bottom-mounted structure. Good agreement between the model results and experimental data are achieved, demonstrating the capability of the developed model on resolving wave-structure interactions. Thus, the proposed non-hydrostatic model with IB method can provide an alternative to studying wave interactions with complex structures.